2002
DOI: 10.1179/030192302225003477
|View full text |Cite
|
Sign up to set email alerts
|

Experimental examination of slag/refractory interface

Abstract: diVerent thermal expansion coeYcients) which, during the subsequent heating and cooling cycles of the ladle, results Ladle glazes are a thin coating of slag formed when in stresses and eventually to 'spalling' of the refractory. the top slag comes in contact with the refractory Thus, the aims of this research programme were to during draining of the ladle. It is believed that ladle obtain direct evidence that ladle glazes are a major source glazes are a major source of inclusions in the next of inclusions; to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 5 publications
3
57
0
Order By: Relevance
“…The ladle lining (refractory) in their study was magnesite refractory (carbon-bearing MgO lining). Riaz et al 7) and Hassall et al 8) also performed similar studies on the plant ladle treatment with magnesite refractory. The primary concerns of previous studies were to identify the inclusions and to correlate the melt cleanliness (the number of inclusion) and ladle age.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…The ladle lining (refractory) in their study was magnesite refractory (carbon-bearing MgO lining). Riaz et al 7) and Hassall et al 8) also performed similar studies on the plant ladle treatment with magnesite refractory. The primary concerns of previous studies were to identify the inclusions and to correlate the melt cleanliness (the number of inclusion) and ladle age.…”
Section: Introductionmentioning
confidence: 71%
“…The feasibility of the physical detachment can be supported by the microstructure of the glaze layer showing the existence of spinel particles on the interface of glaze and molten steel. Several previous studies [7][8][9][10][11] for the ladle glaze of a magnesite lining also suggested that the particles like MgO originally formed in the glaze layer can be retained in the liquid steel as inclusions. For example, Beskow and Du Sichen 10) reported that the complex inclusion of liquid CaO-Al 2 O 3 (-MgO-SiO 2 ) bearing MgO particles, one of the typical inclusions in a practical ladle treatment, was most probably originated from the ladle glaze itself.…”
Section: Molten Steel and Inclusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[191] slag melt [89,152,153] ) found that ''glazed refractories'' and ''reaction layers at the surface of bricks'' formed with molten steel at 1550°C to 1600°C. [151,153,200] The compositions of manganese aluminosilicate inclusions (MnO-Al 2 O 3 -SiO 2 system) found in forgings, ladle glaze analysis, and reaction layers formed between refractory and liquid steel are compared in Figure 31. [88] In this figure, the liquid steel is killed mainly by silicon and manganese alloys and a small amount of aluminum.…”
Section: Slag Properties Such As Interfacial Tensionmentioning
confidence: 99%
“…Lining refractory [89,[148][149][150][151][152][153] Analysis of the lining refractory composition before and after operations can be used to estimate inclusion absorption to the lining and the lining erosion. Also, the origin of a complex oxide inclusion can be traced to lining refractory erosion by matching the mineral and element fractions in the slag with the inclusion composition.…”
Section: Slag Composition Measurementmentioning
confidence: 99%